Difference between revisions of "1966 IMO Problems/Problem 4"
(→Solution) |
(→Solution) |
||
Line 1: | Line 1: | ||
== Solution == | == Solution == | ||
− | Assume that \frac{1}{\sin{2x}}+\frac{1}{\sin{4x}}+\dots+\frac{1}{\sin{2^{n}x}}=\cot{x}-\cot{2^{n}x is true, then we use n=1 and get \cot x - \cot 2x = \frac {1}{\sin 2x} | + | Assume that \frac{1}{\sin{2x}}+\frac{1}{\sin{4x}}+\dots+\frac{1}{\sin{2^{n}x}}=\cot{x}-\cot{2^{n}x} is true, then we use n=1 and get \cot x - \cot 2x = \frac {1}{\sin 2x} |
+ | |||
+ | First, we prove \cot x - \cot 2x = \frac {1}{\sin 2x} | ||
+ | |||
+ | LHS=\frac{\cos x}{\sin x}-\frac{\cos 2x}{\sin 2x} | ||
+ | |||
+ | = \frac{2\cos^2 x}{2\cos x \sin x}-\frac{2\cos^2 x -1}{\sin 2x} | ||
+ | |||
+ | =\frac{2\cos^2 x}{\sin 2x}-\frac{2\cos^2 x -1}{\sin 2x} | ||
+ | |||
+ | =\frac {1}{\sin 2x} | ||
+ | |||
+ | Using the above formula, we can rewrite the original series as | ||
+ | |||
+ | \cot x - \cot 2x + \cot 2x - \cot 4x + \cot 4x \cdot \cdot \cdot + \cot 2^{n-1} x - \cot 2^n x | ||
+ | |||
+ | Which gives us the desired answer of \cot x - \cot 2^n x |
Revision as of 08:12, 24 September 2010
Solution
Assume that \frac{1}{\sin{2x}}+\frac{1}{\sin{4x}}+\dots+\frac{1}{\sin{2^{n}x}}=\cot{x}-\cot{2^{n}x} is true, then we use n=1 and get \cot x - \cot 2x = \frac {1}{\sin 2x}
First, we prove \cot x - \cot 2x = \frac {1}{\sin 2x}
LHS=\frac{\cos x}{\sin x}-\frac{\cos 2x}{\sin 2x}
= \frac{2\cos^2 x}{2\cos x \sin x}-\frac{2\cos^2 x -1}{\sin 2x}
=\frac{2\cos^2 x}{\sin 2x}-\frac{2\cos^2 x -1}{\sin 2x}
=\frac {1}{\sin 2x}
Using the above formula, we can rewrite the original series as
\cot x - \cot 2x + \cot 2x - \cot 4x + \cot 4x \cdot \cdot \cdot + \cot 2^{n-1} x - \cot 2^n x
Which gives us the desired answer of \cot x - \cot 2^n x